AN ISLAMIC PERSPECTIVES, THE CURRENT STATE OF INDONESIA IN THE GLOBALIZATION ERA - Mas'ud, Riduan; El-badriati, Baiq; Azizurrohman, Muhammad (IAIN Tulungagung, 2022)
Abstract: Countries must be able to compete due to the high global intensity of trade and agreements. As a first step in dealing with this, many countries employ economic concepts that are tailored to their specific circumstances. The goal of this research is to look at the role of Islamic economics in dealing with the onslaught of economic globalization, such as China's Belt Road Initiative (BRI), and multi-sectoral institutions like the IMF and the World Bank. The literature research approach used in this paper is qualitative using literature review method. The results of this study found that the Indonesian government was in the midst of a powerful wave that required strong captains and ships. In other words, the existence of BRI, IMF and World Bank will be a threat if they are not controlled properly. As a result, the government has to divert this funding to productive areas such as agriculture. Furthermore, given China's concentration on Islamic banking, Indonesia may be able to persuade China to involve the Indonesian people in developing its products. Furthermore, the Indonesian government must be able to read every step taken by BRI, IMF, and World Bank so as not to be trapped in debt investment. Keywords: Islamic economic, belt road initiative, IMF, worldbank